RANCANG BANGUN ROBOT PENGANGKUT BARANG DENGAN KOMBINASI SENSOR ULTRASONIK DAN BLUETOOTH MODULE - Fauzia Ichtiaratul Rizqi; Najwa Sheila Kamilia Arzaq; Riska Yohanari; Sahli Tri Atmaja; Tateng Sukendar (Ensiklopedia of Journal, 2026)
This study presents the design and prototype of a low‑cost cargo‑carrying robot based on Arduino Uno, integrating an HC‑SR04 ultrasonic sensor for obstacle detection and an HC‑05 Bluetooth module for wireless control. DC motors driven by an L298N/L293D provide locomotion, powered by two 3.7 V batteries. The work covers hardware design, firmware development, and prototype testing in a confined environment. Experimental results show reliable obstacle detection and effective remote control, with acceptable load‑carrying capability despite limitations in motor power and sensor response. The prototype serves as a foundation for improved control algorithms and power optimization.Keywords: Mobile robot; Obstacle avoidance; Wireless control; Arduino Uno